Basic Concepts in Population Modeling, Simulation, and Model‐Based Drug Development—Part 2: Introduction to Pharmacokinetic Modeling Methods. (17th April 2013) - Mould, DR; Upton, RN
Abstract : Population pharmacokinetic models are used to describe the time course of drug exposure in patients and to investigate sources of variability in patient exposure. They can be used to simulate alternative dose regimens, allowing for informed assessment of dose regimens before study conduct. This paper is the second in a three‐part series, providing an introduction into methods for developing and evaluating population pharmacokinetic models. Example model files are available in theSupplementary Data online. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e38; doi:10.1038/psp.2013.14 ; advance online publication 17 April 2013